Epizootiology in contemporary global health: making a difference in the health of people in West Africa (2011)
Global health in contemporary times has thrown up challenges that demand innovative and pragmatic approaches and one of such is the concept of One Health. Towards this end, a holistic approach of tackling human and a n i d health problems is being explored in order to bring about poverty alleviation, health and food security particularly in developing countries. To achieve this, there is an increasing role and importance of epizootiology in planning and evaluation of projects for control and prevention of pandemic from animal diseases in West Africa. Since there is a critical shortage of available manpower in this area, filling this gap requires training of public and private personnel that are focused on diseases at human-animal health interface. Therefore, under the flagship of epizootiology, we propose an initiative that brings together teachers that have worked in this area and have similar and complementary skills and expertise that trainees would be able to assimilate. This program which has received support at the University of Ibadan, Nigeria, will work along with a consortium of Universities to increase graduate training in the surveillance of human-animal diseases from 2012. It is anticipated that this platform will produce a critical mass of highly trained personnel within West Africa that will make a difference in tackling the ever challenging health needs of the people in the sub-region